1989
DOI: 10.1139/z89-105
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic behaviour of resident killer whales (Orcinus orca) off Vancouver Island, British Columbia

Abstract: Recordings of underwater vocalizations and behavioural observations were collected from 16 photographically identified resident pods of killer whales (Orcinus orca) off Vancouver Island, British Columbia, during 1978–1983. Vocalizations recorded during 43 days spent with three representative pods were analyzed for each of five activity states: foraging, travelling, group-resting, socializing, and beach-rubbing. The whales produced three types of sounds that were assumed to be social signals: discrete calls, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
508
1
10

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(540 citation statements)
references
References 38 publications
21
508
1
10
Order By: Relevance
“…Samarra et al (2010) reported two different types of killer whale HFM signals with the two call types exhibiting similar structure, but with higher and lower frequency content. If the two signal types recorded in SCB were produced by different individuals, HFM signals could be used to identify individual group members or maintain group cohesion as described for discrete calls (Ford, 1989). The higher frequency content and lack of consistent down-sweeps of signals recorded in the Atlantic by Samarra et al (2010) may be a consequence of the spatial separation and variable use of high frequency signals between the populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samarra et al (2010) reported two different types of killer whale HFM signals with the two call types exhibiting similar structure, but with higher and lower frequency content. If the two signal types recorded in SCB were produced by different individuals, HFM signals could be used to identify individual group members or maintain group cohesion as described for discrete calls (Ford, 1989). The higher frequency content and lack of consistent down-sweeps of signals recorded in the Atlantic by Samarra et al (2010) may be a consequence of the spatial separation and variable use of high frequency signals between the populations.…”
Section: Resultsmentioning
confidence: 99%
“…Killer whales (Orcinus orca) produce a variety of acoustic signals including echolocation clicks for foraging and pulsed calls and whistles for communicative purposes (Ford, 1989). Killer whale echolocation clicks and pulsed calls have distinct characteristics, which together allow for the discrimination to species level (Au et al, 2004;Barrett-Lennard, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resident pods possess unique vocal repertoires of stereotyped pulsed calls with primary energy between 1 and 6 kHz (Ford, 1989). These calls contain both a high-frequency component (HFC between 2 and 12 kHz, Hoelzel & Osborne, 1986) beamed forward from the melon and a less directional low frequency component (LFC between 80 and 2400 Hz, Ford, 1987).…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%
“…The relative energy of these two components may cue conspecifics into the orientation of the signaler (Miller, 2002). Discrete, stereotyped calls constitute the majority of vocalizations in most behavioral contexts (Ford, 1989). Hitherto, the individual call type has largely been regarded as an arbitrary and interchangeable unit without any specific behavioral significance.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%